2017
DOI: 10.1080/14786419.2017.1375924
|View full text |Cite
|
Sign up to set email alerts
|

A new anti-inflammatory meroterpenoid from the fungus Aspergillus terreus H010

Abstract: An unusual austinoid, 1,2-dehydro-terredehydroaustin (1), together with two known meroterpenoids (2 and 3), were isolated from the mangrove endophytic fungus Aspergillus terreus. The structures were elucidated on the basis of spectroscopic data, X-ray diffraction and ECD calculations. The anti-inflammatory activity was assayed and compound 1 exhibited weak inhibition effect against the production of nitric oxide (NO) in lipopolysaccharide (LPS)-induced RAW 246.7 mouse macrophages with an IC value of 42.3 μM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…In a similar research, Chen et al ( 2017 ) reported that culture extracts of the endophytic fungus Lasiodiplodia theobromae isolated from A. ilicifoliu s showed anti-inflammatory activities and they isolated some active components from the extracts including Lasiodiplactone A, an unprecedented lactone that possesses a unique tetracyclic system. Compounds such as meroterpenoid identified from Aspergillus terreus H010, an endophytic fungus from Kandelia obovata , also exhibited anti-inflammatory activities (Liu et al 2017 ). Results from these reports and those from our study strongly support the view that endophytic fungi of mangrove plants are promising sources of natural bioactive compounds (Stierle et al 1993 ; Strobel et al 1997 ; Strobel and Daisy 2003 ; Chen et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a similar research, Chen et al ( 2017 ) reported that culture extracts of the endophytic fungus Lasiodiplodia theobromae isolated from A. ilicifoliu s showed anti-inflammatory activities and they isolated some active components from the extracts including Lasiodiplactone A, an unprecedented lactone that possesses a unique tetracyclic system. Compounds such as meroterpenoid identified from Aspergillus terreus H010, an endophytic fungus from Kandelia obovata , also exhibited anti-inflammatory activities (Liu et al 2017 ). Results from these reports and those from our study strongly support the view that endophytic fungi of mangrove plants are promising sources of natural bioactive compounds (Stierle et al 1993 ; Strobel et al 1997 ; Strobel and Daisy 2003 ; Chen et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the fermentation supernatant and mycelia of these fungi presented antibacterial activities [ 17 ]. Previous studies discovered and tested the anti-inflammatory effects of A. terreus derived compounds, such as butenolide derivatives [ 18 , 19 ] and meroterpenoids [ 20 ]. A butyrolactone I analogue, asperteretal A, significantly decreased the NO production in RAW264.7 cells [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The stereochemistry configurations of known compounds, preaustinoid A2, isoaustinol, dehydroaustin, and dehydroaustinol, were first determined by XRD, and the latter three molecules displayed anti-acetylcholinesterase (anti-AchE) activity (IC 50 = 0.4~3 µM) [101]. An unusual austinoid, 1,2-dehydro-terredehydroaustin (327), from the mangrove-derived fungus Aspergillus terreus H010, showed weak anti-inflammatory (NO) effects in RAW 246.7 cells (IC 50 42.3 µM vs. 30.7 µM for indomethacin) [102]. The marine endophytic fungus of the brown alga, Aspergillus sp.…”
Section: Aspergillus Spmentioning
confidence: 99%